Comparing Media Systems Beyond the Western World - Hallin, Daniel C.; Mancini, Paolo (Cambridge : Cambridge University Press, 2011)
Comparing Media Systems Beyond the Western World offers a broad exploration of the conceptual foundations for comparative analysis of media and politics globally. It takes as its point of departure the widely used framework of Hallin and Mancini's Comparing Media Systems, exploring how the concepts and methods of their analysis do and do not prove useful when applied beyond the original focus of their 'most similar systems' design and the West European and North American cases it encompassed. It is intended both to use a wider range of cases to interrogate and clarify the conceptual framework of Comparing Media Systems and to propose new models, concepts and approaches that will be useful for dealing with non-Western media systems and with processes of political transition. Comparing Media Systems Beyond the Western World covers, among other cases, Brazil, China, Israel, Lebanon, Lithuania, Poland, Russia, Saudi Arabia, South Africa and Thailand.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).